FROM FACE-TO-FACE COMMUNICATION TO DIGITAL INTERACTION: AN EXPLORATION OF THE GEN Z COMMUNITY IN NORTH SUMATRA - Hanif Maulana Pratama; Irwansyah Irwansyah (Journal Analytica Islamica, 2026)
The use of TikTok as a short-video social media platform has transformed the way Generation Z builds social interaction and relationships. This study aims to identify changes in communication practices and social relations among Generation Z resulting from the use of TikTok. The research employed a qualitative approach with a case study design focusing on the Generation Z community in Kelurahan Kota Matsum, Sumatera Utara. Informants were selected using purposive sampling with the criteria of Generation Z individuals who actively use TikTok, with a total of six informants. Data were collected through in-depth interviews and non-participant observation. The data were analyzed using thematic analysis techniques. The findings reveal that the use of TikTok encourages changes in communication practices from face-to-face communication toward digital interaction characterized by visual, brief, and symbolic forms. Social relationships among Generation Z tend to become more flexible and fluid, and are no longer entirely dependent on physical proximity. Social relations are interpreted as digitally mediated connections influenced by self-representation and audience responses. In addition, TikTok’s algorithm plays a role in shaping social connectivity through content visibility mechanisms. These findings indicate that TikTok functions as a digital social space as well as a primary medium in the transformation of Generation Z communication practices from face-to-face interaction to digital interaction. The study implies that the dominance of digital interaction reshapes the quality of social relations and social cohesion among Generation Z at the local community level, highlighting the need for adaptive communication strategies to maintain a balance between digital interaction and face-to-face communication.